1999
DOI: 10.1091/mbc.10.2.393
|View full text |Cite
|
Sign up to set email alerts
|

The Small MrRas-like GTPase Rap1 and the Phospholipase C Pathway Act to Regulate Phagocytosis inDictyostelium discoideum

Abstract: The function of the small-M r Ras-like GTPase Rap1 remains largely unknown, but this protein has been demonstrated to regulate cortical actin-based morphologic changes in Dictyostelium and the oxidative burst in mammalian neutrophils. To test whether Rap1 regulates phagocytosis, we biochemically analyzed cell lines that conditionally and modestly overexpressed wild-type [Rap1 WT(ϩ)], constitutively active [Rap1 G12T(ϩ)], and dominant negative [Rap1 S17N(ϩ)] forms of D. discoideum Rap1. The rates of phagocytosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 58 publications
1
76
0
2
Order By: Relevance
“…Because the small G protein Rap1 has been demonstrated to provide a supportive role in Dictyostelium protrusion generation and substrate adhesion, we examined how the expression of the dominant negative Rap1S17N-myc would affect adhesion in the confirmed RAM strains (41)(42)(43)(44)(45). In wild-type cells, Rap1S17N has been shown to increase myosin IIB at the cell cortex which leads to cell retraction and decreased adhesion (44).…”
Section: Phenotypes Of the Rams Mutants Are Strongly Correlated And Dmentioning
confidence: 99%
“…Because the small G protein Rap1 has been demonstrated to provide a supportive role in Dictyostelium protrusion generation and substrate adhesion, we examined how the expression of the dominant negative Rap1S17N-myc would affect adhesion in the confirmed RAM strains (41)(42)(43)(44)(45). In wild-type cells, Rap1S17N has been shown to increase myosin IIB at the cell cortex which leads to cell retraction and decreased adhesion (44).…”
Section: Phenotypes Of the Rams Mutants Are Strongly Correlated And Dmentioning
confidence: 99%
“…Nevertheless, other micropinocytic uptake mechanisms likely exist in this organism, as cells overexpressing Rap1, a member of the Ras-like superfamily of GPTases, show a 60% reduction in fluid-phase uptake but completely lack visible macropinocytic structures (Seastone et al 1999). It is also noteworthy that detergent insoluble lipid rafts, which have been implicated in caveolae-mediated endocytosis in mammalian cells, were found in D. discoideum (Xiao and Devreotes 1997).…”
Section: Uptake Mechanismsmentioning
confidence: 99%
“…Actin cross-linking proteins and small guanosine triphosphatases (GTPases) of the Rac and Rho family that regulate and organise the actin cytoskeleton are important in the process of ruffle extension in D. discoideum (Seastone et al 1998;Seastone et al 1999). A subset of actin-binding proteins associate transiently with the phagocytic cup of amoebae such as talin (Niewohner et al 1997) and coronin, which is thought to regulate the G-to F-actin equilibrium (Maniak et al 1995).…”
Section: Molecular Aspects Of the Internalisation Processesmentioning
confidence: 99%
“…Rap proteins have been detected in the endo/phagocytic compartment (59) and have been shown to play a role in phagocytosis in Dictyostelium (44). In mammalian phagocytes, they may contribute to phagocytosis by mediating the activation of integrins, as shown in lymphoid cells (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…Rap1 regulates phagocytosis in Dictyo- stelium (44) and is required for complement receptor-mediated phagocytosis (45). We previously demonstrated that engagement of Fc␥R cross-activates the complement receptor, CR3, a member of the integrin family, enabling cells to recognize and bind complement-opsonized particles (32).…”
Section: Rap1 Gtpase Is Activated By Diacylglycerol and Modulates Cromentioning
confidence: 99%